Language use, language choice and language attitudes among young Mauritian adolescents in secondary education - Bissoonauth, Anu (1998)
The present study reports on a research project conducted in Mauritius in 1992/93. The project was designed to investigate patterns of language use, language choice and language attitudes of a subsection of the Mauritian population: adolescents in full-time education.